2020
DOI: 10.1088/1402-4896/abc20e
|View full text |Cite
|
Sign up to set email alerts
|

Solar energy application for LFR unit with trapezoidal cavity receiver considering radiative mode

Abstract: In current article, influence of radiation and convection modes on behavior of air inside an absorber in trapezoidal shape has been investigated. Such cavity is part of Linear Fresnel Reflector (LFR) unit and it is important to analyze such geometry to reach higher performance. Properties of carrier fluid were assumed as function of temperature. To involve radiation effect, discrete ordinates model was implemented. Influences of external convective factor (hext), Angle of adiabatic wall (θ), temperature ratio … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 21 publications
(22 reference statements)
0
4
0
Order By: Relevance
“…The evaporation rate for In 2 Se 3 was ∼24 -Å s . 1 The surface roughness of the films was measured vial roughness monitor/profilometer (SOLID IN II). The metallic point contacts on the surface of MoO 3 /In 2 Se 3 layers were prepared with the help of a bar-like masks of areas of 0.2´0.7 cm 2 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The evaporation rate for In 2 Se 3 was ∼24 -Å s . 1 The surface roughness of the films was measured vial roughness monitor/profilometer (SOLID IN II). The metallic point contacts on the surface of MoO 3 /In 2 Se 3 layers were prepared with the help of a bar-like masks of areas of 0.2´0.7 cm 2 .…”
Section: Methodsmentioning
confidence: 99%
“…Recent technology developments are associated with many varieties including renewable energy [1,2], computer based information technology sectors [3], 3-D printing technology [4] and communication technology sectors [5]. Communication technology occupies important roles in almost every field of human operation such as education sectors, medical field, banking sectors, agricultural sector and field of engineering [6].…”
Section: Introductionmentioning
confidence: 99%
“…They concluded that the heat loss reduction rate varied from 6.36% to 13.55% when turning off the movable cover was applied. Ebrahimpour et al [8] investigated the influence of radiation and convection modes on the behavior of air for linear Fresnel reflector (LFR) with trapezoidal cavity receiver. Temperature difference augments about 180% when adiabatic wall angle enhances as temperature ratio is 0.8.…”
Section: Introductionmentioning
confidence: 99%
“…Scientists have tried to improve novel methods to grow the rate of heat transfer in heat mechanisms, resulting in grown performance of the thermal mechanisms, decreased fuel consumption and also economic benefits [1][2][3][4][5][6][7][8][9][10][11][12]. Nonetheless, it is obvious that the addition of nanopowders to typical fluids results in profound augmentation in heat conductivity.…”
Section: Introductionmentioning
confidence: 99%